Copper foil, secondary battery comprising same, and method for manufacturing same
By forming a specific treatment stack on the surface of the copper foil and controlling the surface roughness, the problem of crushing and peeling of the silicon-based electrode during the lithiation process is solved, and the number of cycles and total capacity of the battery is improved.
Patent Information
- Application Number
- CN202380044211.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-11
AI Technical Summary
The existing silicon-based electrodes are easily crushed and peeled off during the lithiation process, and the solid electrolyte interface is unstable, resulting in a short battery life and safety hazards. At the same time, the volume changes of the silicon-based negative electrode during charging and discharging lead to delamination of the current collector and loss. Electrochemical contact.
By forming a treatment stack, including a structured layer and a functional layer, on both surfaces of the copper foil, the surface roughness is controlled in the range of 1.0 to 3.0 μm, to ensure good adhesion between the copper foil and the silicon negative electrode.
It improves the resistance of the current collector, extends the number of charging and discharging cycles, and enhances the total capacity and life of the battery.
Smart Images

Figure CN119422254A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of copper foil, and more particularly to a current collector, an electrode and a silicon secondary battery including the copper foil. Background Art
[0002] Energy storage devices (including batteries and capacitors) are used in a variety of applications. Due to their relatively high energy density, relatively high specific energy, light weight and potentially long life, it is desirable to use advanced rechargeable batteries in a wide variety of consumer electronics, electric vehicles, grid storage and other important (future) applications. However, despite the increasing commercial penetration of lithium (Li)-ion batteries, there is still a need for further development of these batteries, particularly for potential applications in low or zero emission, hybrid electric or all-electric vehicles, drones, consumer electronics, energy-efficient cargo ships and locomotives, aerospace applications and the power grid.
[0003] Currently, graphite is commonly used commercially as a material for negative electrodes in rechargeable lithium-ion batteries because of the reversible insertion of lithium ions without significant volume (about 10%) and morphological changes. The relatively low specific capacity of graphite (370 mAh / g) is its main disadvantage, which limits the specific capacity of lithium-ion batteries. Due to the high theoretical specific lithium ion storage capacity of silicon of about 3579 mAh / g compared to other materials, silicon is regarded as a promising alternative to carbon-based negative electrodes for various types of rechargeable batteries. In practice, lower capacities can be achieved. To date, silicon has been commercialized mainly as a reinforcing additive for carbon-based negative electrodes, although alternative production methods for silicon-based and carbon-free negative electrodes have been developed in the past few years. For example, WO 2021 / 029769 A1 discloses a battery including a negative electrode made of silicon and a method for manufacturing such a negative electrode using chemical vapor deposition.
[0004] One obstacle to the full realization of silicon-based electrodes is the fact that Li-Si electrodes experience a high degree of pulverization and exfoliation as well as an unstable solid electrolyte interface (SEI) during the lithiation process. The decomposition of active silicon materials will lead to a shorter battery life and may potentially cause safety issues due to short circuits in the battery. Another obstacle is the large volume change of silicon-based negative electrodes during charging and discharging, which can be up to 300%, while carbon-based negative electrodes experience only 10% volume change. Such volume changes can cause the silicon-based negative electrode to delaminate from the current collector, resulting in a loss of electrochemical contact. When the silicon particles are no longer in contact with the current collector, electron transfer is no longer possible, and the silicon particles become ineffective substances, thereby reducing the overall capacity of the battery.
[0005] The current collector typically comprises a copper foil. Treatments are proposed to enhance the adhesion of the copper foil to the silicon anode, for example coating the copper foil with a layer comprising zinc oxide and / or tin oxide, as proposed in WO2021 / 029769A1. While this known treatment is a satisfactory first step in the right direction, allowing the battery to maintain its capacity over 20 charge-discharge cycles, there is not enough performance for silicon-based anodes to achieve the performance currently achieved by carbon-based anodes, i.e. maintaining the battery capacity over hundreds of charge-discharge cycles. Therefore, there is a need for improved current collectors with higher resistance to delamination to allow an increase in the number of charge and discharge cycles.
[0006] Purpose of the Invention
[0007] An object of the present invention is to provide an improved copper foil for use in a current collector of a secondary battery which is free from the above-mentioned problems. Summary of the invention
[0008] In order to achieve the above-mentioned object, the present invention proposes a treated copper foil for use in a secondary battery, the treated copper foil having a first side and a second side opposite to the first side, and comprising a copper foil having two opposite surfaces and a processing stack arranged on each surface of the copper foil. One side of the treated copper foil corresponds to the surface of the copper foil having its corresponding processing stack. The processing stack includes a structured layer for controlling / influencing surface roughness and at least one functional layer for imparting one or more customized functions.
[0009] According to the present invention, the treated copper foil provides the following surface roughness characteristics on each of the first side and the second side:
[0010] - a surface roughness Rz (ISO) between 1.0 and 3.0 μm, preferably between 1.5 and 2.5 μm; and
[0011] - Surface roughness Sk, called core height, between 1.0 and 3.0 μm.
[0012] In other words, both treated sides of the treated copper foil of the present invention exhibit surface roughness that satisfies the specified ranges of roughness parameters Rz and Sk.
[0013] Ideally, the values of Rz and Sk are the same on both sides, or at least as similar as possible. However, in practice, due to manufacturing tolerances, there may be differences in the values of Rz and / or Sk from one side to the other. In addition, in the case of electrolytic copper foil, the matte (electrolyte) side and the polished side may have different initial roughness profiles, which will affect the roughness of the treated side.
[0014] In practice, the same treatment can be applied to both surfaces of the copper foil. However, due to variations in the initial surface roughness of the (untreated) copper foil, the two sides of the treated copper foil may have different surface roughnesses while still within the specified range. It should be understood that this difference primarily reflects initial variations and has nothing to do with the structuring treatment performed to form the structured layer.
[0015] In summary, a treatment stack is formed on the surface of the base copper foil to achieve specified surface roughness characteristics. This can be accomplished using conventional techniques and processes for both structured and functional layers.
[0016] The present invention is based on the inventors' discovery that a specific surface roughness profile or a specific surface state of a treated copper foil is desirable for a treated copper foil to be used in a secondary battery, in particular as a current collector in a battery, and on the identification of the corresponding surface roughness characteristics.
[0017] Thus, one of the advantages of the present invention is the determination that specific surface conditions represented by a range of 2D and 3D surface roughness parameters, and more specifically by a conventional roughness parameter Rz in combination with Sk, are suitable for accurately characterizing the surface roughness of treated copper foils (particularly but not limited to copper foils) for use as current collectors in batteries (particularly rechargeable Li-ion batteries). For this application, the relevant 3D surface roughness characteristics were found to be particularly relevant. Indeed, compared to contact measurements (such as Rz), 3D surface roughness characteristics, also called "non-contact" in the art because they are determined using a microscope, bring refined information about the surface roughness.
[0018] In other words, one of the advantages of the present invention is that it determines that a specific surface roughness characterized by the surface roughness Rz and Sk values specified herein is suitable for a treated copper foil to be used in an electrode assembly, particularly as a negative current collector in a negative electrode assembly.
[0019] It should be understood that the inventors unexpectedly found that the use of the copper foil of the present invention as an electrode leads to improved behavior in charge / discharge cycles. In fact, the inventors found that, with such a surface roughness profile, it is possible to ensure good adhesion of the treated copper foil to an electrode material attached thereto or coated thereon, such as, but not limited to, a Si-based electrode material.
[0020] More specifically, the inventors found that having an Rz within the specified range of 1.0 to 3.0 μm is necessary but not sufficient to ensure satisfactory behavior in charge / discharge cycles, and that copper foil providing only a surface roughness of both Rz and Sk within the specified range of 1.0 to 3.0 μm allows the desired improved behavior to be achieved when used in an electrode assembly.
[0021] According to the present invention, when used, both the first and second sides of the treated copper foil provide Rz between 1.0 μm and 3.0 μm and Sk between 1.0 μm and 3.0 μm, and an electrode material such as a silicon layer will be formed on each side of the two sides of the copper foil.
[0022] First test results using Si-based negative electrodes comprising the copper foil of the invention show that the treated copper foil of the invention brings about a higher resistance to delamination and allows an increased number of charge and discharge cycles.
[0023] The specified roughness profile of the treated copper foil is mainly influenced by the structured layer which will largely control the overall roughness.
[0024] Although Rz has been the main parameter used in the industry to characterize the roughness of copper foils, the inventors have found that it can be advantageously supplemented by other surface roughness parameters such as Sk, and that the surface of the treated copper foil of the present invention can therefore be characterized in an appropriate and reproducible manner, wherein the specified values of Rz and Sk provide enhanced charge / discharge behavior that has heretofore not been achievable using conventional copper foils for electrodes.
[0025] The inventors have determined that a suitable value for Sk of the treated copper foil is 1-3 μm. A lower Sk may result in the treated copper foil being too smooth to properly adhere to another layer of material, while a higher Sk (corresponding to a highly rough foil) may prevent a continuous and / or uniform layer from forming thereon.
[0026] Surface roughness Sk, or simply Sk, also called core roughness depth or core height, is a measure of the core roughness (peak-to-valley) of a surface removing the extreme peaks and valleys (maximum height peaks and minimum height valleys), and is derived from the area material ratio curve.
[0027] Since Sk is affected by both the texture (number and size of peaks and valleys) and the spatial arrangement and spacing of the peaks and valleys, this parameter can advantageously further differentiate between surfaces with similar roughness (as represented using a 2D parameter such as Rz). In general, Sk will increase with the spatial complexity of the texture, regardless of whether Rz changes.
[0028] In an embodiment, the treated copper foil has a thickness of 50 to 190 g / m 2 The treated copper foil is preferably as uniform as possible, with little to no thickness variation. In this article, referring to the area weight used to characterize the copper foil is similar to referring to the thickness of the foil, because the foil has a substantially constant thickness. The treated copper foil with the highest area weight is the thickest, while the treated copper foil with the lowest area weight is the thinnest.
[0029] Such treated copper foils are thin enough to be cost-effectively produced and provide desirable conductive properties for use in rechargeable or secondary batteries. In such applications, the thinner the copper foil, the higher the gravimetric energy density.
[0030] Preferably, the treated copper foil of the present invention has a thermal conductivity of 30 to 100 kgf / m 2 Such a treated copper foil can advantageously resist elongation caused by the surface increase of a layer attached thereto or coated thereon (e.g., a silicon layer that expands or contracts by insertion or desorption of Li ions during charge and discharge of a battery including the treated copper foil as a current collector and a silicon layer as a negative electrode).
[0031] Preferably, the treated copper foil has an elongation of between 3% and 30%. Thus, the treated copper foil can advantageously stretch sufficiently to accommodate the surface increase of a layer attached thereto or coated thereon (such as an electrode layer), while not being able to stretch sufficiently to form a buckle when the layer attached thereto or coated thereon experiences a surface decrease, thereby preventing the formation of areas on the copper foil that are not attached thereto or coated therewith (e.g., an electrode) layer.
[0032] In an embodiment, the copper foil is an electrolytic copper foil, i.e., the copper foil is prepared by electrolytic deposition / electroplating of copper. As known in the art, the surface roughness of the untreated copper foil affects the surface roughness of the treated copper foil. Preferably, for both surfaces, the base copper foil (especially the electrolytic copper foil) has a surface roughness Rz (ISO) between 1.0 μm and 2.5 μm, preferably between 1.3 μm and 2.4 μm, and more preferably between 1.5 μm and 2.2 μm.
[0033] In an embodiment, the structured layer is formed by electrodepositing a structured copper layer having a predetermined roughness directly on the untreated side of the copper foil. The structured layer is typically formed from adjacent deposits of copper blocks / shapes that will provide a controlled alternation of peaks and valleys on the surface.
[0034] In particular, the structured layer may comprise or consist of copper nodules deposited directly on the (untreated) side of the copper foil, preferably conventionally covered with a copper plating layer for fixing / encapsulating the nodules on the surface of the copper foil. In other words, the structured layer may be directly on one side of the untreated copper foil and may comprise copper nodules, and preferably a continuous copper layer above the copper nodules. The deposition of copper nodules is well known in the art. The copper nodules may generally have a spherical and / or elliptical shape.
[0035] Preferably, the copper nodules are elliptical in shape (with the main extension being substantially perpendicular to the surface of the copper foil) and have a height between 1.2 μm and 3.0 μm, preferably between 1.8 μm and 2.4 μm, and a diameter between 0.6 μm and 1.1 μm, preferably between 0.7 μm and 0.9 μm. One advantage of depositing elliptical copper nodules may be an increased developed surface, and therefore an increased surface roughness (measured in Sk), relative to the same foil with spherical copper nodules. In fact, since the elliptical nodules are taller than spherical nodules of similar diameter, higher peaks and valleys are formed per unit surface, resulting in a larger interface.
[0036] In an embodiment, the process stack comprises at least one functional layer selected from:
[0037] - a heat-resistant layer mainly comprising zinc and / or nickel,
[0038] - an anti-corrosion layer comprising mainly chromium, and
[0039] - an adhesion-promoting layer comprising a silane compound, such as an aminosilane.
[0040] The term is here predominantly understood to mean comprising more than 50 wt.%, preferably more than 60 wt.%, 70 wt.% or 80 wt.% of the compound.
[0041] In an embodiment, the heat resistant layer may contain zinc and / or nickel in a total amount of up to 60 mg / m 2 ; The concentrations of nickel and zinc are 0-30 mg / m 2 However, the minimum amount of nickel and / or zinc in this layer is 3 mg / m 2 In some embodiments, the heat-resistant layer comprises a total amount of 22 to 32 mg / m 2 of zinc and / or nickel.
[0042] In an embodiment, the anti-corrosion layer comprises 2-10 mg / m 2 , preferably 4-8 mg / m 2 , for example 6 mg / m 2 The amount of chromium.
[0043] In an embodiment, the adhesion promoting layer comprises 3-20 mg / m 2 , preferably 5-15 mg / m 2 , for example, 10 mg / m 2 The amount of silane.
[0044] In an embodiment, the structured layer comprises 5-20 g / m 2 , preferably 8-12g / m 2 The amount of copper.
[0045] Preferably, the treatment stack contains all three layers, with the heat resistant layer being the inner layer (on the structured layer), the anti-corrosion layer in the middle, and the adhesion promoting layer as the outer layer.
[0046] Alternatively, the functional layer may be formed as a combination of zinc, nickel and / or chromium covered by an adhesion promoting layer.
[0047] The functional layer is typically a continuous layer and may be formed by any suitable / known method.
[0048] Preferably, the treatment stack, and in particular the structured layer, provides a thickness defined by the nature and amount of the treatment layer, regardless of the thickness of the (untreated) copper foil. The thickness of the treatment stack is primarily defined by the thickness of the structured layer, which in an embodiment is defined by the size of the copper nodules.
[0049] According to another aspect, the present invention relates to the use of the treated copper foil of the present invention as a current collector for a secondary battery. Advantageously, and as described above, the inventors have found that such treated copper foil of the present invention exhibits suitable mechanical properties and surface roughness to adhere to an electrode, particularly for use as a current collector, preferably in a secondary battery.
[0050] According to yet another aspect, the invention also relates to an electrode assembly comprising a current collector and an electrode, the current collector comprising the treated copper foil according to the first aspect of the invention and the electrode comprising a silicon layer (greater than 50 wt. % Si).
[0051] The copper foil of the present invention is particularly developed to support the Si-based layer. Depending on the manufacturing method, the amount of silicon in the silicon layer can be at least 90%, typically at least 95% and possibly at least 99%. This electrode is a silicon-based electrode rather than an electrode based on Si-doped carbon. The electrode preferably mainly contains silicon. However, it is still within the scope of the present disclosure that the electrode can contain other chemical components, such as hydrogen (silicon is amorphous silicon) or trace amounts of nitrogen, phosphorus, boron, aluminum and / or carbon as doping elements to increase conductivity and / or improve the crystal structure of silicon. It should be understood by those skilled in the art that an electrode containing a silicon layer can be formed by any suitable method, such as physical or chemical vapor deposition, sputtering, electron beam evaporation or application and calcination of a slurry containing silicon. These are particularly suitable for high Si content. In a preferred embodiment, a silicon layer can be formed by chemical vapor deposition of silicon, more preferably by low-pressure plasma enhanced chemical vapor deposition. One advantage of this formation method is that the silicon formation process is a self-organized and spontaneous process for forming a continuous silicon layer. According to the same or other embodiments, the silicon layer has a thickness between 5 and 30 μm.
[0052] However, more conventional methods may be used to form the silicon layer, such as conventional wet slurry coating, albeit with lower Si content (still greater than 50 wt. %).
[0053] In an embodiment, a silicon layer is formed on each of the first side and the second side of the treated copper foil.
[0054] According to yet another aspect, the present invention also relates to a secondary battery comprising an electrolyte, a positive electrode assembly, a negative electrode assembly, a separator layer and a lithium salt compound (usually with associated electrolyte additives), wherein the negative electrode assembly comprises the treated copper foil of the present invention or the electrode assembly according to the present invention.
[0055] According to yet another aspect, the present invention also relates to a method for preparing a copper foil as claimed in claim 16 .
[0056] The resulting treated copper foil comprises a treated stack on both surfaces, the exposed sides of the treated stack each providing a surface roughness Rz between 1.0 μm and 3.0 μm, preferably between 1.5 μm and 2.5 μm, and a Sk between 1.0 μm and 3.0 μm.
[0057] Step b) corresponds to a structuring process or a structuring treatment or a roughening treatment and may also be referred to as electrodeposition of fine copper particles or copper nodules. This method is very effective for obtaining a copper foil surface with a desired texture (or 3D configuration or roughness).
[0058] The copper concentration and bath temperature of the structuring process are usually lower than the corresponding parameters defined for electroplated copper foil, resulting in the formation of discrete copper particles or nodules rather than a continuous layer. The structuring process of step b) is followed by a subsequent step (step c) of conventional copper plating to form a continuous copper layer over the nodules on each side of the copper foil. The formed copper nodules are thus firmly attached to the copper foil. Step c) can be performed directly after step b by passing through another electroplating bath containing a higher concentration of copper.
[0059] In steps c) and d), continuous layers are formed on the copper foil surface and these layers are relatively thin compared to the structured layer. Therefore, these layers tend to follow / reproduce the surface roughness of the structured layer. In other words, the functional layer is a relatively thin layer that does not significantly change the surface roughness of the treated copper foil, which is mainly determined by the initial roughness of the base copper foil and the structured layer.
[0060] Conventional techniques can generally be used to carry out the manufacture of the treated copper foil of the present invention. Electrolytic baths / solutions for functional layer structuring (deposition of nodules) and deposition (passivation / adhesion) are known in the art. They can be used in the context of the present invention. Those skilled in the art can adjust production parameters to provide the desired roughness profile, in particular control nodule shape, more specifically height and diameter.
[0061] Specifically, those skilled in the art of metal electrodeposition are familiar with the theory of Winand and Fischer [see Reference 1], which describes that the type of electrodeposition depends on two main parameters: the ratio of current density to diffusion-limited current density (i.e., metal concentration) and the inhibition strength (e.g., temperature / agitation).
[0062] However, it will be appreciated that the present invention advantageously provides for the fabrication of elliptical nodules, which is a particularly convenient way to tailor the surface roughness to achieve a desired roughness profile (ie, having a desired range of Rz and Sk).
[0063] A preferred electroplating bath for step b) contains 15 to 30 g / L of copper, preferably in the form of copper ions Cu 2+ and 50 to 150 g / L of sulfuric acid. An alternative and equally preferred electroplating bath for step b) comprises 5 to 25 g / L of copper, preferably in the form of copper ions Cu 2+ and 30 to 90 g / L, preferably 40 to 80 g / L of sulfuric acid. The applied current density may be 15 to 30 A / dm 2 Between, preferably between 20 and 30 A / dm 2 The bath is preferably kept at a temperature between 20° C. and 30° C. The deposition duration (immersion length) may be between 5 seconds and 10 seconds.
[0064] Such an electroplating bath allows to produce a structured layer with copper nodules of a size suitable for achieving the desired roughness parameters, in particular the desired Rz and Sk.
[0065] The preferred electroplating bath for step c) contains 60 to 100 g / L of copper, preferably as copper ions Cu 2+ and 30 to 90 g / L, preferably 40 to 80 g / L of sulfuric acid. The applied current density may be 15 A / dm 2 Up to 30A / dm 2 The bath is preferably kept at a temperature between 40° C. and 60° C. The deposition duration (immersion length) may be between 5 seconds and 10 seconds.
[0066] Preferably, the oval copper nodules are grown by a two-step process, in which steps b) and c) are repeated. That is, a first layer of copper nodules is formed, and the first layer of copper nodules is covered with a continuous copper layer. Then a second layer of copper nodules is formed, followed by the deposition of a continuous copper layer. Experience has shown that the second layer of copper nodules tends to form on the first layer of copper nodules. Thus, an oval shape is formed due to the combination of forms. These steps are performed on both sides of the copper foil, preferably in sequence, but can be performed simultaneously.
[0067] One repetition was considered sufficient to obtain a spheroid form (by combining two overlapping nodules); however, this should not be construed as limiting - more repetitions are contemplated.
[0068] It may be noted that since the base copper foil, nodules and capping / encapsulating copper foil are formed by electrodeposition, they consist of pure copper, ie have a copper content of at least 99 wt. %, or even 99.9 wt. %.
[0069] Further details and advantages of the present invention will become apparent from the following detailed description of several non-limiting embodiments, with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] The present invention will now be described by way of example with reference to the accompanying drawings, in which:
[0071] Figure 1 : is a schematic cross-sectional view of a treated copper foil according to the present invention;
[0072] Figures 2 to 4 : are SEM (scanning electron microscope) images of the copper foil according to the present invention at different magnifications;
[0073] Figures 5 to 8 : This is the SEM image of the copper foil for comparison;
[0074] Fig. 9 is a schematic curve showing the area material ratio curve and the determination of the parameter Sk;
[0075] Fig.10 : is a schematic diagram of a copper foil with structural treatment, explaining how to estimate the height of the nodules; and
[0076] Fig.11 : is a diagram illustrating the deposition of oval copper nodules according to an embodiment. DETAILED DESCRIPTION
[0077] As explained above, the present invention provides a treated copper foil having a specific surface roughness. Figure 1, the treated copper foil according to the present invention will be described. The treated copper foil 1 has a first side 1a and a second side 1b opposite to the first side, and includes a copper foil 2 having two opposite surfaces 2a, 2b. The copper foil 2 is also individually referred to as a base copper foil, and its two surfaces 2a and 2b can be referred to as untreated surfaces.
[0078] A treatment stack 3 is formed on each of the two untreated surfaces 2a, 2b. The treatment stack 3 comprises a structured layer 4 and at least one functional layer 5. In the described embodiment, the structured layer comprises nodules 6 or fine copper particles covered by a continuous layer 7 of copper. It may be noted that for the purpose of explanation, Figure 1 Layer 7 is shown with significant height in FIG; in reality, copper layer 7 can be quite thin and will follow the shape of the nodule, such as Fig.11 The roughness of the treated copper foil 1 characterizes the roughness corresponding to the side faces 1 a , 1 b , ie the roughness of the surfaces 2 a , 2 b of the copper foil 2 modified by the treatment of the stack 3 , in particular by the structured layer 4 .
[0079] This treated copper foil is produced by subjecting an untreated copper foil produced by rolling (rolled copper foil) or electrodeposition (electrodeposited copper foil) to at least a structuring (i.e., roughening) process. In an embodiment, the structuring process consists of growing (i.e., forming) nodules (also called fine copper particles) on both sides (i.e., surfaces) of the untreated copper foil.
[0080] Electrodeposited copper foil is produced by using an electroforming unit (referred to in the industry as an electroplater), which is preferably used as a starting / substrate copper foil (or electrolytic copper foil). In the electroforming unit, an electrolyte is passed through a device comprising a rotating drum-shaped positive electrode (whose surface is made of stainless steel or titanium) and a fixed negative electrode (a lead or titanium electrode covered with a precious metal oxide) provided opposite to the positive electrode. An electric current is passed through the two electrodes to deposit copper with a desired thickness on the surface of the positive electrode, thereby forming an electrodeposited copper foil. The electrodeposited copper foil is then peeled off from the surface of the positive electrode and wound onto a storage reel. The foil thus prepared is generally referred to as untreated copper foil.
[0081] For example, a rolled copper foil having a predetermined thickness may be manufactured through a known process of hot rolling, cold rolling, homogenizing, and degreasing an ingot obtained by melting and casting a pure copper material.
[0082] In a subsequent step, the untreated copper foil is subjected to a surface structuring (i.e. roughening) process / treatment. Preferably, in this process, fine copper particles (i.e. copper nodules) are generated on the surface 2a, 2b of the copper foil (by electrolysis) by reducing copper ions. The size of the nodules generally depends on the duration of the electrolysis.
[0083] An exemplary electrolyte for nodule treatment (referred to as a nodule bath) contains 20 g / L of copper ions Cu 2+ and 60 g / L sulfuric acid. The electrolyte can be kept at room temperature (e.g., about 20° C.). A current density slightly higher than that typically used to produce electrodeposited copper foil can be used, e.g., about 30 A / dm 2 Electrolysis is performed. Fine copper particles (ie, copper nodules) are generated on the surface of the copper foil by reducing copper ions, and grow according to the duration of electrolysis (eg, 6 seconds).
[0084] The formation of the copper nodules on the untreated side is immediately followed by a conventional copper plating subsequent step, which is carried out using an electrolyte with a higher copper concentration, at a higher temperature and a higher current density, to form a continuous copper layer over the nodules on each side of the copper foil. The formed copper nodules are thus firmly attached to the copper foil, whereby this step is also referred to as encapsulation.
[0085] An exemplary electrolyte for a copper plating process (referred to as an encapsulation bath) may contain 60 g / L of copper ions Cu 2+ and 60 g / L sulfuric acid. The electrolyte can be maintained at 50°C. A current density slightly higher than that normally used to produce electrodeposited copper foil (e.g., about 15 A / dm 2 ) for electrolysis, and the duration of electrolysis can be, for example, 6 seconds.
[0086] It should be noted that those skilled in the art of metal electrodeposition are aware of the conditions required to form particulate metal deposits. However, the present invention relies on the discovery of a specific relationship between the surface conditions described by Rz and Sk and the charge / discharge cycles of the battery.
[0087] In particular, the inventors have found a particularly advantageous way of structuring copper layers by ellipsoidal copper nodules. In principle, ellipsoidal nodules can be formed as a single metal deposition layer by selecting suitable deposition parameters and adjusting the deposition / residence time to grow ellipsoidal particles.
[0088] Preferably, in order to facilitate industrialization, and in particular for productivity, the oval nodules are preferably formed in a two-step process, that is, the steps of nodule treatment and copper plating can be repeated on each side, such as Fig.11 This method is suitable for forming oval copper nodules on copper foil traveling at conventional speeds (ie, about 15 to 30 m / min).
[0089] from Fig.11It can be seen that an untreated copper foil 2 is subjected to a first structuring treatment on one of its sides 2a or 2b to deposit a first layer of copper nodules 10 in a nodule bath; subsequently a thin copper layer 11 is deposited in an encapsulation bath. In this first step, the nodules 10 are quite round / spherical. Then, the same steps are carried out using, for example, the same nodule bath and encapsulation bath: a second layer of copper nodules 12 is formed - which is also substantially round / spherical, and in turn encapsulated by a thin continuous copper layer 7. Then the other side 2b or 2a of the copper foil 2 is subjected to a similar process.
[0090] It can be observed that the nodules of the second layer are generally deposited on the nodules of the first layer, the combination forming an overall oval shape.
[0091] Without wishing to be bound by any theory, it is believed that because the current is concentrated on the peaks and because the copper concentration in the nodule bath is insufficient for copper ions to reach the valleys between already deposited copper nodules, the nodules of the second layer are preferentially formed over the nodules of the first layer.
[0092] In a subsequent step, the structured copper foil is subjected to an electrochemical or chemical surface treatment to form at least one functional layer over the structured layer comprising copper nodules. The surface treatment may be, for example, an adhesion enhancement treatment and / or a passivation treatment.
[0093] According to a non-limiting embodiment, at least one functional layer is formed by subjecting the structured copper foil to at least one of the following processing steps:
[0094] Electroplating of a zinc layer. For example, depending on the desired deposition amount, this can be accomplished using a coating containing 0.80 g / L zinc and 0.95 g / L CrO 3 The bath was at pH = 3.8 and 4 A / dm 2 The current density is carried out for a certain length of time.
[0095] Electroplating of a nickel layer. For example, depending on the desired deposition amount, this can be accomplished using a catalyst containing 5.0 g / L nickel and 40.0 g / L H 3 BO 3 The bath uses 1.5A / dm at pH = 3.5 2 The current density is carried out for a certain length of time.
[0096] Electroplated chromium layer. For example, depending on the required deposition amount, this can use a chromium layer containing 0.95 g / L CrO 3 The bath was used at pH = 2.0 with 1A / dm 2 The current density is carried out for a certain length of time.
[0097] Zinc passivation and nickel passivation are often considered as alternatives. First, a zinc passivation layer or a nickel passivation layer is formed, and then a chromium layer is formed.
[0098] Typically, zinc and / or plating can be performed to deposit up to 30 mg / m 2 The minimum amount of zinc and nickel in the passive layer is 3 mg / m 2 .
[0099] Chromium plating can be performed to deposit 2 to 10 mg / m 2 of chrome.
[0100] Finally, for the purpose of promoting adhesion, a silane compound layer may be formed as an outer layer. The silane compound layer may be formed by passing through a bath containing 0.4 g / L of Si (as aminosilane). This optional layer may contain 3 to 20 mg / L of 2 of silane compounds.
[0101] Example
[0102] Electrolytic copper foils with an initial surface roughness Rz between 1.0 μm and 3.0 μm were produced by methods well known in the art. The produced untreated copper foils were then subjected to a structuring process according to the invention (Examples 1 to 3) or not subjected to a structuring process (Comparative Examples 1 and 2, not part of the invention).
[0103] Then the copper foil with structured layer according to the present invention (Examples 1 to 3) was subjected to functional treatment to continuously deposit three functional layers, namely a layer containing zinc, a layer containing chromium, and a layer containing a silane compound. Each of the three functional layers is a continuous layer, and the total thickness of the functional layers is between 5nm and 50nm.
[0104] The structured or unstructured copper foils of the comparative examples were subjected to no nodule treatment and no functional treatment other than chrome passivation (Comparative Examples 1 and 2), subjected to nodule treatment and functional treatment similar to one of the copper foils according to the invention (Comparative Example 3), and subjected to a different nodule treatment with the same functional treatment (Comparative Example 4).
[0105] The surface roughness observed by SEM microscope is shown in Figures 2 to 8 middle:
[0106] - Figures 2 to 4 Corresponding to Examples 1, 2 and 3 respectively;
[0107] - Figures 5 to 8 These correspond to Comparative Examples 1 to 4, respectively.
[0108] The copper foils obtained were then analyzed to determine their surface properties such as surface roughness (measured in Rz and Sk, both according to ISO standards) and to determine some mechanical properties such as area weight, tensile strength and elongation.
[0109] A secondary battery including a silicon negative electrode and the treated copper foil according to Examples 1-3 or Comparative Examples 1-4 as a negative electrode current collector was then manufactured according to a method known in the art and not described in further detail herein.
[0110] The copper foil was analyzed as follows.
[0111] Determination of surface roughness Rz
[0112] The roughness of the copper foil in Rz is measured using a contact profilometer consisting of a diamond needle (stylus) sliding on the surface. A 2D profile of the surface is generated from this measurement, and Rz is calculated as the average distance between the highest peak and the lowest valley over 8 sampling lengths. Here, surface roughness Rz refers to ISO 4287:1997.
[0113] Determine the surface roughness Sk
[0114] The Sk parameter (core height) is measured using non-contact 3D white light interferometry. Here, the surface roughness Sk refers to ISO 25178-2 2021.
[0115] The Sk core height is calculated as the height difference at the area material ratio of 0% and 100% on the contour line. Specifically, it is a value obtained by subtracting the minimum height from the maximum height of the core surface. Fig. 9 The determination of Sk is shown in FIG.
[0116] The area-material ratio represents an area having a specific height c or higher. The area-material ratio curve of an area is a curve representing the height at which the area-material ratio changes from 0% to 100%. The contour line is a line where the sum of square deviations in the direction of the vertical axis is the smallest in the central part. The central part of the area-material ratio curve is defined as the position where the secant line has the minimum gradient (inflection point).
[0117] The section of the contour line between two height positions where the area material ratio is 0% and 100% is called the core surface. The peak with a height above the core surface is called a reduced peak, and the valley below the core surface is called a reduced valley. Sk is calculated as the height difference at the area material ratio of 0% and 100% on the contour line; specifically, it is the value obtained by subtracting the minimum height from the maximum height of the core surface.
[0118] The principle of white light interferometry is to split a light beam into two paths, directing one to a reference mirror and the other to the sample surface. The measurement beam travels different distances depending on the surface profile. The two waveforms are then recombined and a specific interference pattern is generated based on their phase difference. These patterns are analyzed to calculate the height of the sample at each point (pixel) scanned. The area material ratio curve is then calculated from this 3D profile, which is typically 155μm x 116μm (i.e., approximately 18000μm 2 ) is measured on the sample surface.
[0119] In the context of the present invention, and for the measurement of Sk of the Examples and Comparative Examples, a microscope model VK-X100 from Keyence was used.
[0120] It should be noted that the area material ratio curve shows the height that varies according to the area material ratio. The measuring device (interferometer) used to determine the area material ratio curve and the mathematical calculation method or model do not affect the curve. In other words, regardless of the measuring device and the mathematical method, the same curve is obtained, and the only possible variability is related to the sensitivity of the measuring device and therefore to the accuracy of the obtained values. On the obtained area material ratio curve, the tangent at the inflection point is determined. The maximum height and the minimum height of the core surface are defined as the intersection between the tangent and the height axis at an area material ratio of 0% and 100%, respectively. Sk is then calculated by subtracting the minimum height from the maximum height of the core surface.
[0121] Imaging treated copper foil
[0122] The treated copper foils produced according to the invention and the comparative examples were imaged using a scanning electron microscope (SEM) THERMO FISHER, Prisma E at a voltage of 20 kV and a tilt of 30° at a magnification between 1000 and 6000.
[0123] Determine the height and diameter of the nodule
[0124] As can be seen from the SEM images, the nodules tend to grow into particles that may be round (spherical) or, particularly for Examples 1-3, more elongated (ellipsoidal) particles in a direction fairly perpendicular to the copper foil surface.
[0125] Methods for characterizing the size (ie, diameter and height) of nodules are proposed.
[0126] The nodule diameter was determined from the SEM image. The diameters of 10 nodules were measured, and then the arithmetic mean and standard deviation were calculated from the measured values and are shown in Table 1.
[0127] The nodule height is evaluated as follows. The weight area of the structured copper foil is measured, and the weight area of the structured layer is estimated by subtracting the weight area of the untreated copper foil from the weight area of the structured copper foil (or treated copper foil, because the weight of the functional foil is relatively negligible). The theoretical thickness of the flat and smooth structured layer is then determined as follows:
[0128]
[0129] The height of the nodules was then estimated as twice the theoretical thickness, assuming that the nodules formed a pyramidal pattern on the surface of the copper foil. Fig.10 Shown in.
[0130] Determining mechanical properties
[0131] Tensile strength and elongation were determined according to IPC TM 650 2.4.18.
[0132] Tensile strength and elongation at break were determined by mechanical force testing at ambient temperature at a tensile speed of 2.0 inches / minute using test specimens measuring 6 x 1 / 2 inches cut out of the (treated) copper foil as test specimens.
[0133] The elongation is determined as follows:
[0134]
[0135] The tensile strength was determined as follows:
[0136]
[0137] The average cross-sectional area is determined as follows:
[0138]
[0139] Determine the area weight by weighing the sample and calculating the area weight as follows:
[0140]
[0141] The measurement was performed 5 times for each of Examples and Comparative Examples, and the corresponding arithmetic mean values are shown in Table 1 as the elongation, tensile strength and area weight values.
[0142] Determine the number of cycles at which greater than 80% of the initial capacity is retained
[0143] The cells including the treated copper foil as the negative current collector and the silicon negative electrode were cycled at an irreversible capacity of about 600 mAh / gram silicon, and the retained capacity was measured after each cycle.
[0144] The last column of Table 1 indicates the number of cycles achieved at the following ratios:
[0145] QN / Q1x100≥80%
[0146] Where Q1 is the initial discharge capacity and QN is the discharge capacity at the Nth cycle.
[0147] Such testing is routine in the art.
[0148] Discussion of Examples and Comparative Examples
[0149] Table 1 provides the surface characteristics, mechanical properties, and the number of cycles at which more than 80% of the initial capacity is retained for the treated copper foils according to the present invention and according to comparative examples.
[0150] All copper foils have a g / m 2 The area weights were similar to those of the samples and the tensile strengths were similar (Table 1).
[0151] Furthermore, all treated copper foils corresponding to the present invention (Examples 1 to 3) had a Sk between 1.0 μm and 3.0 μm and a Rz between 1.0 μm and 3.0 μm, and an elongation between 3% and 30%.
[0152] By comparing the results obtained for Examples 2 and 3 with those obtained for Comparative Examples 1 and 2, it should be noted that these four copper foils have very similar areal weights and tensile strengths (Table 1), but the cells comprising the treated copper foil according to the invention retain more than 80% of their initial capacity at a much higher number of cycles than the cells comprising the comparative copper foil (Table 1). Unlike the foils of Comparative Examples 1 and 2 (see Table 1), the cells comprising the treated copper foil according to the invention retain more than 80% of their initial capacity at a much higher number of cycles than the cells comprising the comparative copper foil. Figure 5 and Figure 6 ), Examples 2 and 3 were subjected to a structuring process (see Figure 3 , corresponding to Example 2, and Figure 4 , corresponding to Example 3). The presence of nodules (or fine copper particles) at the copper foil surface and the resulting higher surface roughness, especially higher Sk, allow for better adhesion of the treated copper foil to the silicon negative electrode and higher battery capacity retention. As is clear from Comparative Examples 1 and 2, having an Rz within the specified range of 1.0 to 3.0 μm is not sufficient to ensure a satisfactory number of cycles to retain more than 80% of the initial capacity. If Sk is below 1.0 μ m, then a battery including such a copper foil loses more than 20% of its initial capacity after less than 10 cycles.
[0153] Referring now to Comparative Examples 3 and 4, the formation of nodules on the copper foil is not sufficient to ensure satisfactory retention of the battery capacity during charge-discharge cycles. If the treated copper foil is too rough (Comparative Example 3) or too smooth (Comparative Example 4), the performance is not optimal. Compared to batteries containing treated copper foils according to the present invention, the capacity is lost more quickly (see Table 1, Comparative Examples 3 and 4 and, for example, Example 1).
[0154] Furthermore, Comparative Examples 1, 2 and 4 exhibit a surface roughness (in terms of Rz) that is very similar to the surface roughness of the treated copper foil according to the present invention. However, the capacity retention of Comparative Example 4 is lower than the capacity retention that can be achieved using the copper foil according to the present invention. One explanation would be that the comparative foil is not in fact rough enough when considering 3D and non-contact parameters such as Sk, and certainly not as rough as the inventive foil. Characterizing the roughness of the treated copper foil primarily by 2D and contact parameters such as Rz is not sensitive enough to understand the actual roughness of the foil and explain the achieved performance. As mentioned above, an advantage of the present invention is therefore to determine a certain surface roughness condition that can be characterized with higher sensitivity by its Rz and further by the parameter Sk, which surface roughness condition enhances the performance of the copper foil as a negative current collector and the capacity retention of a battery comprising such a copper foil.
[0155] Only the treated copper foil corresponding to the invention (ie the foil providing, in addition to Rz between 1 μm and 3 μm, an Sk between 1 μm and 3 μm) allows achieving the desired retention of the battery capacity upon charge-discharge cycling.
[0156] References
[0157] [REF.1]R.WINAND,'Electrocristallisation.Théorie et applications',JOURNAL DE PHYSIQUE IV Colloque C1,supplement au Journal de PhysiqueIII,Volume 4,janvier 1994,C1-55to C1-73.
[0158]
Claims
1. A treated copper foil (1) for use in a secondary battery, the treated copper foil having a first side (1a) and a second side (1b) opposite to the first side, the treated copper foil comprising a copper foil (2) having two opposite surfaces (2a, 2b) and a treatment stack (3) arranged on each of the surfaces (2a, 2b) of the copper foil (2), the side of the treated copper foil corresponding to the surface of the copper foil having its corresponding treatment stack; in, The processing stack comprises a structured layer (4) and at least one functional layer (5), wherein each of the first side (1a) and the second side (1b) has an Rz between 1.0 μm and 3.0 μm, preferably between 1.5 μm and 2.5 μm, and an Sk between 1.0 μm and 3.0 μm.
2. The treated copper foil according to any one of the preceding claims, wherein The copper foil is an electrolytic copper foil, and wherein both surfaces thereof provide a surface roughness Rz between 1.0 μm and 2.5 μm, preferably between 1.3 μm and 2.4 μm, more preferably between 1.5 μm and 2.2 μm.
3. The treated copper foil according to any one of the preceding claims, wherein The structured layer is formed by directly electrodepositing a structured copper layer having a predetermined roughness on the corresponding surface of the copper foil.
4. The treated copper foil according to claim 3, wherein The structured layer comprises copper nodules (6) deposited directly on the surface (2a, 2b) of the copper foil.
5. The treated copper foil according to claim 4, wherein The copper nodules are oval and have a height between 1.2 μm and 3.0 μm, preferably between 1.8 μm and 2.4 μm, and a diameter between 0.6 μm and 1.1 μm, preferably between 0.7 μm and 0.9 μm.
6. The treated copper foil according to any one of the preceding claims, wherein The process stack includes at least one of a heat-resistant layer including zinc or nickel, an anti-corrosion layer including chromium, and an adhesion-promoting layer including a silane compound.
7. The treated copper foil according to any one of the preceding claims, wherein The treated copper foil has a g / m 2 area weight.
8. The treated copper foil according to any one of the preceding claims, wherein The treated copper foil has a strength of 30 kgf / mm at 20°C. 2 Up to 100kgf / mm 2 The tensile strength between.
9. The treated copper foil according to any one of the preceding claims, wherein The treated copper foil has an elongation between 3% and 30%.
10. Use of the treated copper foil according to any one of the preceding claims as a current collector for a secondary battery.
11. An electrode assembly comprising a current collector comprising the treated copper foil of any one of claims 1 to 9 supporting an electrode comprising a silicon layer, wherein the amount of silicon in the silicon layer is greater than 50%, preferably at least 90%, more preferably greater than 95% or 99%.
12. An electrode assembly according to the preceding claim, wherein: The silicon layer is formed by chemical vapor deposition of silicon, preferably by low-pressure plasma enhanced chemical vapor deposition of silicon.
13. The electrode assembly according to claim 12, wherein: The silicon layer has a thickness between 5 μm and 30 μm.
14. The electrode assembly according to any one of claims 11 to 13, wherein: The silicon layer is formed on each side of the treated copper foil.
15. A secondary battery comprising an electrolyte, a positive electrode assembly, a negative electrode assembly, a separator layer and a lithium salt compound, wherein: The negative electrode assembly comprises the treated copper foil of any one of claims 1 to 9, or wherein the negative electrode assembly is the electrode assembly of any one of claims 11 to 14.
16. A method for producing the treated copper foil of any one of claims 1 to 7, comprising the steps of: a) providing an untreated copper foil (2) having a first surface (2a) and a second surface (2b) opposite to the first surface, preferably an electrolytic copper foil having a surface roughness Rz between 1.0 μm and 2.5 μm on both surfaces; b) performing a texturing treatment (3) on each surface of the copper foil by immersing the copper foil in an electroplating bath to provide a predetermined surface roughness on both sides, c) electroplating an additional continuous layer of copper (7) over the layer comprising the nodules; and d) forming at least one functional layer (5) on the additional continuous layer of copper.
17. The method according to claim 16, wherein: Step b) comprises passing the copper foil through a liquid containing 5 to 25 g / L, preferably in the form of copper ions Cu 2+ and 30 to 90 g / L, preferably 40 to 80 g / L of sulfuric acid, and wherein 15 to 30 A / dm 2 , preferably 20 to 30A / dm 2 The current density is 200 s, with the immersion duration being between 5 and 10 s.
18. The method according to claim 17, wherein: The bath was maintained at a temperature between 20°C and 30°C.
19. The method according to claim 17 or 18, wherein: Steps b) and c) are repeated on each surface to produce copper nodules of elliptical shape and having a height between 1.2 and 3.0 μm, preferably between 1.8 and 2.4 μm and a diameter between 0.6 and 1.1 μm, preferably between 0.7 and 0.9 μm.
20. The method according to any one of claims 16 to 19, wherein: Step c) comprises passing the copper foil through a liquid containing 60 to 100 g / L of copper ions Cu 2+ and 30 to 90 g / L, preferably 40 to 80 g / L of sulfuric acid, and wherein 15 to 30 A / dm 2 , preferably 15 to 25 A / dm 2 The current density is 200 s, with the immersion duration being between 5 and 10 s.
Citation Information
Patent Citations
Silicon composition material for use as battery anode
WO2021029769A1